Strategi Pengembangan Koperasi Melalui Kolaborasi dan Transformasi Digital di Kota Bogor - Yustiana Wardhani; Syarief Gerald Prasetya; Vera Clara Simanjuntak (Jurnal Manajemen dan Organisasi, 2023)
The research aims to identify the influential factors in developing cooperative development strategies in the city of Bogor. Research data using primary data and analysis using quantitative methods with SWOT and AHP analysis. The results of the research on the internal-external (IE) matrix show that the position of cooperative development is in cell one by implementing a growth strategy through vertical integration, by means of backward integration, meaning that in order to develop cooperatives in Bogor City, they must be independent, which means the use of all factors of production rely on the cooperative's own business, both products, human resources and other resources. The results of AHP show that the most prioritized strategy implemented is a strategy of trying to improve information and technology systems so that they can innovate and compete with other similar businesses. Cooperatives can make efforts to increase cooperation with the government and the private sector in the field of science and technology development so that cooperatives can innovate and compete in the market, as well as efforts to increase public trust in cooperatives and the need to make regulations and policies that support the development of cooperatives.